Evaluation of acceptor selectivity of Lactococcus lactis ssp. lactis trehalose 6-phosphate phosphorylase in the reverse phosphorolysis and synthesis of a new sugar phosphate. Issue 8 (3rd August 2017) - Taguchi, Yodai; Saburi, Wataru; Imai, Ryozo; Mori, Haruhide
Abstract: Trehalose 6-phosphate phosphorylase (TrePP), a member of glycoside hydrolase family 65, catalyzes the reversible phosphorolysis of trehalose 6-phosphate (Tre6 P ) with inversion of the anomeric configuration to produce β-d -glucose 1-phosphate (β-Glc1 P ) and d -glucose 6-phosphate (Glc6 P ). TrePP in Lactococcus lactis ssp. lactis (LlTrePP) is, alongside the phosphotransferase system, involved in the metabolism of trehalose. In this study, recombinant LlTrePP was produced and characterized. It showed its highest reverse phosphorolytic activity at pH 4.8 and 40°C, and was stable in the pH range 5.0–8.0 and at up to 30°C. Kinetic analyses indicated that reverse phosphorolysis of Tre6 P proceeded through a sequential bi bi mechanism involving the formation of a ternary complex of the enzyme, β-Glc1 P, and Glc6 P . Suitable acceptor substrates were Glc6 P, and, at a low level, d -mannose 6-phosphate (Man6 P ). From β-Glc1 P and Man6 P, a novel sugar phosphate, α-d -Glc p -(1↔1)-α-d -Man p 6 P, was synthesized with 51% yield. Abstract: : A novel sugar phosphate, α-d -Glc p -(1↔1)-α-d -Man p 6 P, was synthesized by Lactococcus lactis ssp. lactis trehalose 6-phosphate phosphorylase.